Experimental Study on Operating Performance of Ground Source Variable Refrigerant Flow System in Winter - Zheng Xiaowei; Zhang Xu; Zhao Deyin; Luo Zhong (Zhileng xuebao)
The operational characteristics of ground source variable refrigerant flow (GSVRF) system in winter was investigated based on the measured data in GSVRF test rig. The variations of hourly heating capacity, hourly system power consumption and coefficient of performance (COP) of unit under different operation rate and part load ratio (PLR) were obtained. The results of the experiments indicate that the hourly heating capacity and hourly system power consumption increased substantially with the growing amount of operation rate, and the amount of hourly system power consumption is more sensitive to changes in the operating rate; regardless of the operation rate, hourly heating capacity increases with the rise of PLR; hourly system power consumption and COP of unit exhibits concave and convex trends with the rise of PLR, which shows that GSVRF system has more favorable energy efficiency at part load operating conditions .